A Retinotopic Basis for the Division of High-Level Scene Processing between Lateral and Ventral Human Occipitotemporal Cortex - Silson, Edward Harry (J Neurosci, 2015)
In humans, there is a repeated category-selective organization across the lateral and ventral surfaces of the occipitotemporal cortex. This apparent redundancy is often explained as a feedforward hierarchy, with processing within lateral areas preceding the processing within ventral areas. Here, we tested the alternative hypothesis that this structure better reflects distinct high-level representations of the upper (ventral surface) and lower (lateral surface) contralateral quadrants of the visual field, consistent with anatomical projections from early visual areas to these surfaces in monkey. Using complex natural scenes, we provide converging evidence from three independent functional imaging and behavioral studies. First, population receptive field mapping revealed strong biases for the contralateral upper and lower quadrant within the ventral and lateral scene-selective regions, respectively. Second, these same biases were observed in the position information available both in the magnitude and multivoxel response across these areas. Third, behavioral judgments of a scene property strongly represented within the ventral scene-selective area (open/closed), but not another equally salient property (manmade/natural), were more accurate in the upper than the lower field. Such differential representation of visual space poses a substantial challenge to the idea of a strictly hierarchical organization between lateral and ventral scene-selective regions. Moreover, such retinotopic biases seem to extend beyond these regions throughout both surfaces. Thus, the large-scale organization of high-level extrastriate cortex likely reflects the need for both specialized representations of particular categories and constraints from the structure of early vision. SIGNIFICANCE STATEMENT One of the most striking findings in fMRI has been the presence of matched category-selective regions on the lateral and ventral surfaces of human occipitotemporal cortex. Here, we focus on scene-selective regions and provide converging evidence for a retinotopic explanation of this organization. Specifically, we demonstrate that scene-selective regions exhibit strong biases for different portions of the visual field, with the lateral region representing the contralateral lower visual field and the ventral region the contralateral upper visual field. These biases are consistent with the retinotopy found in the early visual areas that lie directly antecedent to category-selective areas on both surfaces. Furthermore, these biases extend beyond scene-selective cortex and provide a retinotopic basis for the large-scale organization of occipitotemporal cortex.